Effects of Vitamin D and Dexamethasone on Lymphocyte Proportions and Their Associations With Serum Concentrations of 25-Hydroxyvitamin D3In Vitro in Patients With Multiple Sclerosis or Neuromyelitis Optica Spectrum Disorder - Cho, Eun Bin; Shin, Jong Hwa; Kwon, Soonwook; Kim, Juhyeon; Seok, Jin Myoung; Kim, Byoung Joon; Min, Ju-Hong (Frontiers in Immunology, 2021)
Background: Clear associations have been found between vitamin D deficiency and several autoimmune diseases including multiple sclerosis (MS). However, the benefits of vitamin D supplementation on disease management remain a matter of debate. Objective and Methods: Patients with MS (N=12) and neuromyelitis optica spectrum disorder (NMOSD; N=12) were enrolled along with 15 healthy controls. Changes in lymphocyte subset proportions during stimulation of their peripheral blood mononuclear cells (PBMCs) with the active form of vitamin D, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), and correlations with serum concentrations of the vitamin D precursor 25-hydroxyvitamin D3 (serum 25(OH)D3) were explored. The impact of 1,25(OH)2D3 stimulation on the expression of vitamin-D-responsive genes in immune cells was also investigated. Results: In both MS and NMOSD, stimulation of PBMCs with 1,25(OH)2D3 followed by steroid suppressed the proliferation of total lymphocytes and T cells. The ratio of CD19+CD27+ memory B cells (Bmem) to all B cells after stimulation with 1,25(OH)2D3 was negatively correlated with serum 25(OH)D3 in MS (Spearman’s ρ=–0.594, p=0.042), but positively correlated in NMOSD (Pearson’s r = 0.739, p=0.006). However, there was no relationship between the ratio of Bmem to CD19+CD24+CD38+ regulatory B cells and serum 25(OH)D3 in either MS or NMOSD. In addition, the level of 1,25(OH)2D3-induced CYP24A1 mRNA expression in PBMCs was significantly and negatively correlated with serum 25(OH)D3 (for ΔCT, r=0.744, p=0.014) in MS. Conclusion: These findings suggest a beneficial impact of stimulation of PBMCs with vitamin D followed by steroid on the T-cell population. The association between patient serum 25(OH)D3 and the proportion of Bmem under immune-cell stimulation differed between MS and NMOSD.